Childhood meat eating and inflammatory markers: The Guangzhou Biobank Cohort Study - Zhang WS; Lam TH; Jiang CQ; Schooling CM; Cheng KK; Leung GM (BMC, 2011)
Abstract Background We hypothesized that socio-economic development could, via nutritionally driven levels of pubertal sex-steroids, promote a pro-inflammatory state among men but not women in developing countries. We tested this hypothesis, using recalled childhood meat eating as a proxy for childhood nutrition, in southern China. Methods We used multivariable linear regression in the Guangzhou Biobank Cohort Study phase 3 (2006-8) to examine the adjusted associations of recalled childhood meat eating, <1/week (n = 5,023), about once per week (n = 3,592) and almost daily (n = 1,252), with white blood cell count and its differentials among older (≥50 years) men (n = 2,498) and women (n = 7,369). Results Adjusted for age, childhood socio-economic position, education and smoking, childhood meat eating had sex-specific associations with white blood cell count and lymphocyte count, but not granulocyte count. Men with childhood meat eating almost daily compared to <1/week had higher white blood cell count (0.33 109/L, 95% confidence interval (CI) 0.10 to 0.56) and higher lymphocyte count (0.16 109/L, 95% CI 0.07 to 0.25). Adjustment for obesity slightly attenuated these associations. Conclusion If confirmed, this hypothesis implies that economic development and the associated improvements in nutrition at puberty may be less beneficial among men than women; consistent with the widening sex differentials in life expectancy with economic development.